Morphometric analysis of lapillus otoliths in two estuarine bioindicator catfish (Siluriformes, Ariidae) from a marine protected area in Brazil - Igor Morais; Elisabete Braga; Juliana Azevedo (Ocean and Coastal Research)
Some fish species can be used as target species and bioindicators of environmental disturbances. In this context, biological indicators such as the length, weight, and height of lapillus otoliths of the ariid species Cathorops spixii and Genidens genidens were considered bioindicators of contamination of the Cananéia-Iguape estuarinelagoon complex (CIELC) in this study. The CIELC is an estuary with spatial and temporal differences regarding its hydrobiochemical properties and this characteristic has been related to changes in biological predictors such as the otolith morphometrics of estuarine fish. Therefore, this study aimed to verify the responses of otolith dimensions to sexual and temporal changes, throughout the CIELC. In total, 163 wild catfish C. spixii and 55 G. genidens were collected during the winter period of 2009, 2017, and 2018 in the CIELC. In general, the weight and length of lapillus otoliths of C. spixii and G. genidens were good metrics adjusted to fish growth. Females of C. spixii were significantly larger than males and subadults and there were no significant differences regarding the sexual approach of G. genidens. The temporal approach showed significant differences between the years for both catfish. C. spixii sampled in 2009 and 2018 showed greater total length (TL) and total weight (TW) when compared with fish from 2014 and 2017 (p < 0.05). G. genidens collected in 2018 had greater TL and TW than the specimens sampled in the other years (p < 0.05). Otolith dimensions seem to have followed this same pattern, since females of C. spixii had higher values for otolith weight, height, and length than males and subadults (p < 0.05). The data obtained in this study can be a potential tool for application combined with other ecological analyses and conservation studies in the CIELC.